THE INFLUENCE OF CONTAINER WEIGHT AND NUMBER OF GANG ON STEVEDORING PRODUCTIVITY - Anindita Anung Permata; Nur Rini; Luqman Khakim (JOBS (Jurnal Of Business Studies), 2018)
The aim of this study is to analyze the influence of container weight and number of gang on stevedoring productivity in Tanjung Emas Semarang Port case at PT Samudera Indonesia Tbk., Semarang Branch. This research used a multiple linear regression carried out by SPSS 22.0 with time series data for 2013-2017 and secondary data from PT. Samudera Indonesia Tbk., Semarang Branch. The result showed that partially, container weight has significant negative influence on stevedoring productivity, and number of gang has significant positive influence on stevedoring productivity. Simultaneously, container weight and number of gang significantly influence stevedoring productivity by 37.7% while 62.3% are influenced by other variables that were not described in this research